Recent Progress in the Preparation of Horizontally Ordered Carbon Nanotube Assemblies from Solution. Issue 6 (23rd January 2018) - Zhang, Jianwei; Cui, Jianlei; Wang, Xuewen; Wang, Wenjun; Mei, Xuesong; Yi, Peiyun; Yang, Xinju; He, Xiaoqiao
Abstract : Carbon nanotubes (CNTs) has been reported for nearly 30 years, but commercial applications is rarely reported. Some reasons for this are related to the CNT properties, especially the electronic properties. Approximately 67% of semiconducting CNTs and 33% of metallic CNTs is usually achieved via a normal synthesis. However, it is difficult to implement a large‐scale, ordered assembly of the CNTs. Currently, there are two mainstream methods for obtaining CNTs arrays. Although great progress has been made with direct growth methods using special techniques, there is still room to simultaneously increase both the density and purity. With the development of purification technology, solution assembly methods has attracted tremendous attention because of their ease of processability, low cost of fabrication, and ability to cover large areas at room temperature. In this review, we highlight solution assembly methods and divide the existing methods into three categories. In each category, we give a detailed description of the specific method including the mechanism, an illustration of the process, achievements, advantages, and disadvantages. Finally, the development trends and the research frontier according to our own understanding is described. In this review, a valuable reference for scholars engaged in related research is provided. Abstract : Horizontally ordered carbon nanotube assemblies from solution means that the carbon nanotubes are dispersed in the solution, and then accurately position them through external force, film‐aided, self‐assembly methods in order to form linear, scale, ordered structure, which expands the application of carbon nanotubes in the field of electronic devices, super material and so on.